Microgenesis of language creativity: Innovation, conformity and incongruence in children's language play. (January 2018) - Cekaite, Asta
Abstract: The study examines young children's engagement in language creativity, in this instance, spontaneous language play. It presents an analysis of peer group interaction in a multilingual preschool setting for 3- to 6-year-olds in Sweden. Combining video-ethnography and detailed interactional analysis, it explores the interactional organization, textual features, evaluative/affective stances and social functions that characterize language play. The theoretical perspective draws on interactional sociolinguistics and the Vygotskian (2004) notion that imagination and creativity are built on patterning (i.e., recognizability), innovative transformations and manipulations of prior materials, experiences and understandings. Here, creativity is shown to be a collective and normatively guided process: it is located in peer group collaborative performances, and involves peer group language, affective and aesthetic socialization. The analysis shows that children's spontaneous language play is characterized by an aesthetic in which that which is incongruent, unexpected and also recognizable is exploited and appreciated. It feeds on the ongoing tension between predictability (routine of culturally recognizable activities) and the novelty/improvisational character of in situ performance. Creative language use serves as a multifaceted locus for aesthetic, affective and normative (ideological) stance taking and mutual socialization. Through their performances, the children socialize each other into sensitivity to what kind of contributions constitute valued verbal genres of the peer group culture.